2022
DOI: 10.3390/vetsci9060287
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Analysis of Leukocyte Populations in the Lung Tissue of Dromedary Camels

Abstract: Respiratory tract infections are among the most common infections in dromedary camels, with a high impact on animal health, production, and welfare. Tissue-specific distribution of immune cells is one of the important factors that influence the nature and outcome of the immune response to pathogens. Several protocols have recently been described for the flow cytometric analysis of immune cells in the lung tissue of several species. However, no such protocol currently exists for dromedary camels. The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…(2013) reported lower percentages of lymphocytes (40.0 ± 14.4) and eosinophil (0.3 ± 0.3) in the BALF of healthy young horses compared to adults (35.3 ± 14.0) and (0.2 ± 0.4) respectively, which was in our present study for lymphocytes (25 ± 2.22) and eosinophil (3.5 ± 0.56) for young camels compared to adult camels (16.67 ± 1.78) and (1.167 ± 0.47), respectively. The difference in the BALF cytology between young and old camels, and the difference in their concentration compared to other animal species, maybe because of the difference in the composition of the immune system and the immune reaction in camels ( Hussen and Schuberth, 2020 ; Hussen et al ., 2022 ). Our study found a higher percentage of epithelial cells in adult camels compared to young’s, which was in arrangement with a previous study ( Finotto et al ., 1993 ), which reported that the higher epithelial cells in the BALF could be explained by injury of lower airways in the bronchial epithelium layer, which may occur after the inhalation of allergens and toxic materials, and through virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) reported lower percentages of lymphocytes (40.0 ± 14.4) and eosinophil (0.3 ± 0.3) in the BALF of healthy young horses compared to adults (35.3 ± 14.0) and (0.2 ± 0.4) respectively, which was in our present study for lymphocytes (25 ± 2.22) and eosinophil (3.5 ± 0.56) for young camels compared to adult camels (16.67 ± 1.78) and (1.167 ± 0.47), respectively. The difference in the BALF cytology between young and old camels, and the difference in their concentration compared to other animal species, maybe because of the difference in the composition of the immune system and the immune reaction in camels ( Hussen and Schuberth, 2020 ; Hussen et al ., 2022 ). Our study found a higher percentage of epithelial cells in adult camels compared to young’s, which was in arrangement with a previous study ( Finotto et al ., 1993 ), which reported that the higher epithelial cells in the BALF could be explained by injury of lower airways in the bronchial epithelium layer, which may occur after the inhalation of allergens and toxic materials, and through virus infections.…”
Section: Discussionmentioning
confidence: 99%